Glucose Tolerance and Left Ventricular Pressure-Volume Relationships in Frequently Used Mouse Strains. (20th January 2011) - Oosterlinck, Wouter; Vanderper, Annelies; Flameng, Willem; Herijgers, Paul
Abstract : We investigated glucose tolerance and left ventricular contractile performance in 4 frequently used mouse strains (Swiss, C57BL/6J, DBA2, and BalbC) at 24 weeks. Glucose tolerance was tested by measuring blood glucose levels in time after intraperitoneal glucose injection (2 mg/g body weight). Left ventricular contractility was assessed by pressure-conductance analysis. Peak glucose levels and glucose area under the curve were higher (all P < .05 ) in C57BL/6J (418 ± 65  mg/dL and 813 ± 100  mg⋅h/dL) versus Swiss (237 ± 66  mg/dL and 470 ± 126  mg⋅h/dL), DBA2 (113 ± 20  mg/dL and 304 ± 49  mg⋅h/dL, P < .01 ), and BalbC mice (174 ± 55  mg/dL and 416 ± 70  mg⋅h/dL). Cardiac output was higher (all P < .05 ) in Swiss (14038 ± 4530  μL/min) versus C57BL/6J (10405 ± 2683  μL/min), DBA2 (10438 ± 3251  μL/min), and BalbC mice (8466 ± 3013  μL/min). Load-independent left ventricular contractility assessed as recruitable stroke work (PRSW) was comparable in all strains. In conclusion, glucose tolerance and load-dependent left ventricular performance parameters were different between 4 mice background strains, but PRSW was comparable.